2010
DOI: 10.1007/s12185-010-0558-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pediatric patients with Langerhans cell histiocytosis treated with 2 chlorodeoxyadenosine: a nationwide survey in Japan

Abstract: The aim of this study was to assess the outcome of treatment with 2-chlorodeoxyadenosine (2-CdA) in pediatric patients with Langerhans cell histiocytosis (LCH) in Japan. We retrospectively identified 17 pediatric LCH patients treated with 2-CdA. All patients were refractory or reactivated cases who had been initially treated according to the JLSG-02 protocol of the Japan LCH study group. At initiation of 2-CdA therapy, 4 patients had primary refractory multisystem (MS) disease with risk organ (RO) involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Cytarabine is a drug also phosphorylated by deoxyctidine kinase and has been used successfully together with vincristine and prednisolone in children with disseminated LCH and organ dysfunction (Egeler et al , ). The main limitation of the study combining and cytarabine was the small number of patients enrolled, nevertheless the results were significantly better than the reported historical outcome for this group of patients (Imamura et al , ).…”
mentioning
confidence: 68%
“…Cytarabine is a drug also phosphorylated by deoxyctidine kinase and has been used successfully together with vincristine and prednisolone in children with disseminated LCH and organ dysfunction (Egeler et al , ). The main limitation of the study combining and cytarabine was the small number of patients enrolled, nevertheless the results were significantly better than the reported historical outcome for this group of patients (Imamura et al , ).…”
mentioning
confidence: 68%
“…In patients who show reactivation in non‐risk organs while they are off therapy, treatment with pamidronate combined with Cox2 inhibitor or 2‐CdA monotherapy may be effective. Careful attention is required to prevent known adverse effects of therapy with 2‐CdA, namely, the development of severe persistent bone‐marrow failure and myelodysplastic syndrome .…”
Section: Treatment and Outcomementioning
confidence: 99%
“…A recent study demonstrated the effectiveness of 2-CdA in children with recurrent LCH. [13] Recurrences are more common when the disease is multifocal than in patients presenting with disease that is confined to a solitary focal point. However, there have been reports of recurrent unifocal tumors.…”
Section: Discussionmentioning
confidence: 99%